Impact of G20 on Financial Inclusion in Indonesia: Microfinance, Financial Technology, and Economic Digitalization - Evi Maria; Alexandria Firsta Putri Aisyah; Edi Sudiarto (The Journal of Financial, Accounting, and Economics, 2025)
Financial inclusion has been a key focus area in the G20 Finance Track, which aims to address and reduce economic disparities through expanding access to financial services. This is particularly relevant for low-income and remote communities, which face various barriers to accessing the formal financial system, be it geographical, infrastructural, or socio-economic. By increasing access to financial products and services such as savings, credit, insurance, and digital payments, financial inclusion is expected to drive economic empowerment, strengthen financial resilience, and reduce poverty. The G20 initiative is an important catalyst in mainstreaming financial inclusion as an inclusive sustainable development strategy. Therefore, it is important to empirically assess the extent of the impact of this policy on real conditions at the micro and macro levels. This study aims to analyze and describe the changes that occur in microfinance institutions, the development of financial technology (fintech), and economic digitalization through e-commerce in Indonesia, especially in the context of the implementation of the G20 agenda. The approach used in this research is descriptive quantitative with a paired sample t-test method to measure the difference between conditions before and after the G20 intervention. The results show that there is a statistically significant increase in a number of financial inclusion indicators after the intervention, especially in the aspects of fintech usage and digital transactions. This finding provides empirical evidence that the G20 plays an important role in accelerating digital financial transformation in Indonesia. Thus, global policies and agendas such as the G20 can have a real and positive impact on financial inclusion at the national level, if adaptively integrated with local needs.